Blasting demolition of steel structure using linear cumulative cutting technology. (November 2017) - Duan, Baofu; Zhou, Yuancheng; Zheng, Shaochen; Bao, Minghao; Wang, Liping; Dong, Jianghui
A cumulative cutting blasting technology was used for cutting a 20-mm-thick steel plate for the demolition of a steel structure. The main factors affecting the outcome of this approach included the opening angle of the liner, the height, and the section form of the charge bed. Based on the theory of linear cumulative cutting, the liner cutter and cutting test were designed to blast the steel plate. The dynamics of the entire process were analyzed with numerical calculation, including jet formation, penetration of targets, and cutting processes. Each parameter of the cutter was analyzed and optimized. Finally, the liner cutter and cutting blasting technology were applied for the demolition of a steel structure arch bridge. The study results provided the theory as well as details of a successful application for the cumulative cutting blasting of large steel structures and other similar projects.